Wake-up workout 10 minutes a day to a better body - Lysycia, Jacqueline (Hamlyn, Octopus Publishing Group Ltd., 2005)
Recent research shows that there are more benefits to be gained from exercising in the morning than at any other time of day. Stretches in bed, yoga salutations, cardio sessions, or exercises for the shower - this book has 10-minute exercise routines to suit your mood and level of fitness.